EVALUASI SISTEM INFORMASI DENGAN MODEL DESIGN-REALITY GAP - Falgenti, Kursehi (Proceedings of KNASTIK, 2012)
To evaluate/analyse the results of information systems projects, many researchers havebeen using TAM, UTAUT, and DeLone and McLean IS Success Model. Design-RealityGap Model was developed by Richard Heeks, this model has been used to evaluateseveral information systems projects in developing countries, such as hospitalinformation system project, e-government, and implementation of ERP project. Thismodel is claimed to provide a comprehensive explanation the cause of the failure orsuccess of information systems projects. This is the experimental study using IS Successmodel and Design Reality Gap Model with case study approach. A research objectSMEs in Jakarta, focus of this study only evaluates the quality system elements in ISsuccess model and Technology element in Design reality Gap Model. ERPImplementation evaluation experiment with these two models produce research outputsthat are complementary.